Motivasi Belajar Anak Speech Delay dalam Perspektif Peran Guru: Studi Deskriptif - Veryawan, Veryawan; Damanik, Ibnu Hajar; Ansari, Khairil (Syifaul Qulub: Jurnal Bimbingan dan Konseling Islam, 2025)
Speech delay is a delay in language or speech development. Motivation is the basis for students to achieve maximum learning outcomes. Teachers also have several roles, one of which is as motivators. Teachers provide motivation and encouragement to their students in achieving learning success. This study used a qualitative method with a descriptive qualitative approach. Data were obtained through in-depth interviews with one teacher and two students with speech delays. Meanwhile, secondary data were obtained from books, scientific papers, and other documents to answer all the questions in this study. The data analysis techniques used were data reduction, data presentation, and conclusion drawing. The results of the study show that the role of teachers, especially for children with speech delays, is very important and has a significant influence on the growth and development of these children. One of these roles is as a motivator for children with speech delays. A good teacher for children with special needs is one who can teach and guide their students to achieve their desired goals. Therefore, do good so that you will be treated well by your students, and do not discriminate against any of them.